Sensory and chemical characterization of Chinese bog bilberry wines using Check-all-that-apply method and GC-Quadrupole-MS and GC-Orbitrap-MS analyses. (January 2022) - Lin, Yanxin; Liu, Yaran; Liu, Shuxun; Kortesniemi, Maaria; Liu, Jiani; Zhu, Baoqing; Laaksonen, Oskar
Graphical abstract: Highlights: Sensory quality and volatile profiles of commercial bog bilberry wines were studied. One third of 148 volatile compounds were detected by high resolution GC-Orbitrap-MS. "Fruity" and "floral" attributes were generally liked, "licorice" and "chili" were disliked. Certain ethyl esters and linalool contributed to positive sensory features. o -Cymene, p -cymenene, and 4-vinylphenol contributed to negative sensory features. Abstract: The sensory and chemical profiles of commercial bog bilberry (BB) wines were investigated using a multi-analytical approach. Sensory test included scaling and check-all-that-apply (CATA) method with questions on liking of BB wine. The sensory data was correlated with their volatile compound profiles determined using gas chromatography coupled with quadrupole and orbitrap mass spectrometry (GC-Quadrupole/Orbitrap-MS). In general, all BB wines were characterized with "fruity", "blueberry" and "floral" odors and "sour", "mouth puckering" and "sweet" flavors. Samples more frequently characterized as "fruity" and "floral" in CATA were preferred by the panelists (n = 93). High relative proportions of o -cymene, p -cymenene, 1-octen-3-one and 3-ethylphenol in a sample (described as "ginger" and "chili") resulted in a lower liking rating. Similarly, generally disliked sample described with "Chinese herbs" and "licorice" was characterized by compounds 3-methylpentan-1-ol, 1, 1, 6-trimethyl-1, 2-dihydronaphthalene, and 4-vinylphenol. The data will give novel information for berry wine and beverage industry on the quality factors of BB wines linked to higher acceptance.